A new subspecies of Zamenis hohenackeri (Strauch, 1873) (Serpentes: Colubridae) based on morphological and molecular data - Hofmann, Sylvia; Mebert, Konrad; Schulz, Klaus-Dieter; Helfenberger, Notker; Göçmen, Bayram; Böhme, Wolfgang (Zootaxa, 2018)
Based on morphological characteristics, two subspecies of the Transcaucasian rat snake (Zamenis hohenackeri) are currently recognized, namely Z. h. tauricus and Z. h. hohenackeri. Both subspecies are repeatedly considered to be conspecific colour morphs, or have even been confused with Z. situla. Although, few studies involved the Transcaucasian rat snake in a phylogenetic approach, none has so far led to any taxonomic changes. We assessed the intraspecific morphological variation and phylogeographic relationships among specimens from different locations across its updated distribution. Our molecular (1191 bp mtDNA, 565 bp nuDNA) and morphological data provide sufficient evidence to support three distinct lineages within the Z. hohenackeri complex with a different arrangement compared to a previous study. These represent the subspecies Z. h. hohenackeri, Z. h. tauricus, and a lineage from southwestern Turkey which is described as a new subspecies. Aspects of historical biogeography and conservation status are briefly discussed.